Integrasi Kearifan Lokal Dalam Naskah Film Untuk Promosi Pariwisata Budaya Lokal - Wahyu Nova Riski; FX Yatno Karyadi (CV. ITTC INDONESIA, 2026)
The integration of local cultural values into film narratives holds significant potential to promote cultural tourism and strengthen creative industries in regional contexts. This study aims to explore and develop strategies for integrating local wisdom into film scriptwriting as a means of promoting culture-based tourism. Using the Art-Based Action Research (ABAR) approach, this research seeks to formulate a creative, participatory, and reflective model of script development that represents local cultural identity while supporting sustainable tourism and the growth of the creative industry.The findings indicate that the integration of local wisdom into film scripts requires an in-depth participatory research approach to ensure that culture functions not merely as a background element but as an active component shaping characters, conflicts, and dramatic structures. Furthermore, the study confirms that the use of artificial intelligence (AI) in scriptwriting remains complementary due to the limited availability of digital data on local cultural content. In this context, AI serves as a tool for idea exploration and narrative mapping rather than a substitute for human creativity.This research also proposes an action research model specifically developed for the needs of film scriptwriting based on local wisdom. The findings contribute to strengthening film studies methodology and offer a new approach to scriptwriting practices that are collaborative, contextual, and culturally grounded.